Epidemiology of Streptococcus pneumoniae Serotypes in Jordan Amongst Children Younger than the Age of 5: A National Cross-Sectional Study - Munir Abu-Helalah; Asma’a Al-Mnayyis; Hamed Alzoubi; Ruba Al-Abdallah; Hussein Jdaitawi; Omar Nafi; Kamel Abu-Sal; Alaa Altawalbeh; Alia Khlaifat; Enas Al-Zayadneh; Ihsan Almaaitah; Ibrahim Borghol; et al. (Vaccines, 2023)
Introduction: Streptococcus pneumoniae infections are a major cause of mortality and morbidity worldwide. In Jordan, pneumococcal conjugate vaccines (PCVs) are not included in the national vaccination program. Due to the current availability of several PCVs, including PCV-10, PCV-13, and PCV-15, along with PCV-20, currently undergoing pediatric approvals globally, the decision to introduce PCVs and their selection should be based on valid local data on the common serotypes of Streptococcus pneumoniae. Methods: This cross-sectional study aimed to identify the frequency of serotypes of Streptococcus pneumoniae in children aged below 5 years hospitalized with invasive pneumococcal diseases (IPDs), including pneumonia, septicemia, and meningitis, during the study’s duration in representative areas of Jordan. Serotyping for culture-positive cases was based on the capsular reaction test, known as the Quellung reaction. qPCR was conducted on the blood samples of patients with lobar pneumonia identified via X-ray or on cerebrospinal fluid for those with a positive latex agglutination test for Streptococcus pneumoniae. Results: This study was based on the analysis of the serotypes of 1015 Streptococcus pneumoniae cases among children younger than the age of 5: 1006 cases with pneumonia, 6 cases with meningitis, and 3 cases with septicemia. Only 23 culture-positive cases were identified in comparison to 992 lobar pneumonia cases, which were PCR-positive but culture-negative, with a PCR positivity rate of 92%. Serotypes 6B, 6A, 14, and 19F were the most common serotypes identified in this study, with prevalence rates of 16.45%, 13.60%, 12.12%, and 8.18%, respectively. PCV-10, PCV-13, PCV-15, and PCV-20 coverage rates were 45.32%, 61.87%, 64.14%, and 68.47%, respectively. Discussion: To the best of our knowledge, this is the largest prospective study from the Middle East and one of the largest studies worldwide showing the serotypes of Streptococcus pneumoniae. It reveals the urgency for the introduction of a PCV vaccination in Jordan, utilizing recently developed vaccines with a broader serotype coverage.